Varieties of Islamisation: varying contexts and changing strategies. By Abdul Rashid Moten. United Kingdom: Cambridge Scholars Publishing, 2023, pp. 190 - Mohamed Zacky, Mohamed Fouz (CENTRIS, 2024)
Abdul Rashid Moten's latest work, "Varieties of Islamization: Varying Contexts and Changing Strategies," is a timely contribution to the ongoing debate on the Islamization of the knowledge (IOK) movement. The IOK has evolved significantly over the past four decades and has encountered many global changes, resulting in its rebranding under various names, such as integration, de-secularization, dewesternization, and de-colonization. However, there is confusion about whether these terms refer to the same project or correspond to different projects with mutually exclusive directions and premises. In addressing these issues, Rashid Moten's work provides a framework that helps readers understand the genesis and later developments and directions of the Islamization movement. As a veteran of the Islamization movement, the author makes it clear that these different brand names are not meaningless and are instead significant. He believes that these different terms sometimes reflect methodological and, at other times, strategic shifts of the IOK discourse. For Rasheed Moten, the evolution of IOK movement symbolizes it’s adaptability and dynamism. To elaborate this point further, the author has structured the book's nine chapters in a way that guides readers in tracing the subtle intellectual moves within the lager Islamization movement over the past few decades.